Functional and Emotional Communication in Digital Healthcare: A SEM-PLS Approach to Service Performance - Sudianto; Aflit Nuryulia Praswati; Yusuf Alam Romadhon (Al-Hijrah Indonesia, 2024)
This study aims to analyze the influence of Instrumental Interaction and Affective Interaction on healthcare service Performance, with Relationship Marketing as a mediating variable, in the context of social media-based marketing at Clinic X. The research is grounded in the growing importance of effective and empathetic communication in building patient trust and loyalty, particularly in the digital era where social media platforms are widely used for healthcare promotion and interaction. A quantitative approach with a hypothesis testing design was employed. Data were collected from 250 patients using an online questionnaire based on a 5-point Likert scale and analyzed using the SEM-PLS method via SmartPLS 3.0. The results show that both Instrumental Interaction and Affective Interaction have a significant effect on Relationship Marketing. However, both interactions demonstrate a negative direct impact on Performance when applied independently, without the support of long-term relational strategies. Meanwhile, Relationship Marketing significantly mediates the effect of both interactions on service performance, although its mediating strength is not dominant. These findings highlight the importance of integrating both functional and emotional approaches in healthcare services, as well as the need for a more holistic, relationship-centered digital marketing strategy. This research provides practical implications for healthcare institutions to enhance service performance by balancing communication with clear medical information and empathetic engagement.